Does size matter in the speed and accuracy on image identification? - Satcharoen, Kleddao (My University, 2017)
Icon images need to be presented in correct sizes and their perceptions must be accurate for the end users to perform appropriate tasks as intended. This study investigates whether six different sizes of icon images affect image identification in terms of response time and accuracy. The results of the experiment show that although a general trend, i.e. the larger the image gets, the lesser response time and more accurate the image identification becomes, appears to hold, the difference of the measurements of response time among some icon images is in fact insignificant. A similar observation is also made for accuracy of image identification. The result of this investigation indicates that a wider and more thorough study of the size issue over commonly used icon images is needed.
Keywords: Human Computer Interaction; Image identification; Image size; Reaction time; Visual search